In situ TEM observation on the interface-type resistive switching by electrochemical redox reactions at a TiN/PCMO interface. Issue 2 (25th November 2016) - Baek, Kyungjoon; Park, Sangsu; Park, Jucheol; Kim, Young-Min; Hwang, Hyunsang; Oh, Sang Ho
Abstract : Interfacial redox reactions that drive the resistive switching of Pr0.7 Ca0.3 MnO3 (PCMO)-based devices were revealed and analyzed via in situ TEM. Abstract : The interface-type resistive switching devices exhibiting bipolar and multi-level resistive switching have been considered as the key component for neuromorphic device applications. To directly observe the microscopic details of underlying electrochemical redox reactions occuring at a metal/oxide interface, we implemented in situ resistive switching of TiN/Pr0.7 Ca0.3 MnO3 (PCMO)/Pt junction devices in a transmission electron microscope (TEM). The in situ TEM observations directly show that an intermediate reaction layer (TiO x N y ), growing and shrinking in the thickness range of a few nanometers at the TiN/PCMO interface in response to the applied voltage, mainly determines the device resistance by limiting the transport of charge carriers via the Poole–Frenkel conduction mechanism. A detailed analysis of in situ TEM observations demonstrates that electrochemical redox reactions at the TiN/PCMO interface are facilitated by the electric field driven drift of oxygen as well as Ti ions with a much stronger influence of the oxygen ions. As such, the reaction kinetics are governed by the electric field acting across the TiO x N y reaction layer. This layer defines the critical field for the onset of switching, which is measured to be of the order of 10 6 V cm −1, a typical value at which the ionic drift velocity starts increasing exponentially with the field according to the nonlinear ionic drift model. The present results indicate that understanding the nature of the electric field driven drift of ions in a nanoscale solid electrolyte is a key to the precise control of the resistive switching of metal/insulator/metal junction devices via voltage stimulations.